PRACTICAL RECOMMENDATIONS ON PLATFORMS AND ACTIVITIES FOR EFL TEACHERS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This research paper aims at providing effective recommendations in terms of digital platforms and educational activities that can be implemented in the classroom by English as a Foreign Language teachers. The research thoroughly examines the effectiveness of digital platforms in terms of resource usefulness and the digital educational environment's influence upon the classroom activities carried out by English teachers. The research paper underlines the effectiveness of educational activities conducted in support of students’ language skill acquisition through communication exercises, audio-visual exercises, gamification methods of studying, and educational material that encourages autodidactic studying. The research’s results underscore the paramount significance of resource-oriented goals and effective engagement of students in the digital educational platform. This research paper provides the reader with effective solutions in improving the methodology process conducted in the classroom by English teachers and underlines the scientific and practical significance of strategic digital platform use in contemporary educational process.